UPAYA PENINGKATAN PRESTASI KERJA PADA SATUAN KERJA PERANGKAT DAERAH DINAS KEHUTANAN KABUPATEN KUTAI BARAT - Anastasius Jimi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze efforts to improve work perfomance in Regional Working Units West Kutai District Forestry Office. The results showed that the performance improvement efforts undertaken Forest Service West Kutai through education and training, incentives, enforcement of labor discipline, provision of working facilities, and the award are very appropriate means to encourage employees to perform better. It is known from the results of interviews with key informants and supported by observations from the object of research which indicates that the accumulative efforts made by 5 (five) parameters provide a meaningful contribution to improving work performance. Despite efforts to improve work performance,they are still confronted by several issues (inhibiting factors), it can be concluded that the performance can be improved by 5 (five) parameters has been carried by West Kutai District Forestry Office.